The birth partner : a complete guide to childbirth for dads, partners, doulas, and other labor companions - Simkin, Penny, 1938-2024; Cheyney, Melissa (Harvard Common Press, 2025)
"For this fully revised sixth edition of this perennial bestseller, birthing expert and practicing midwife Melissa Cheyney, PhD, joins Penny for a better-than-ever, completely up-to-date new book. Since the original publication of The Birth Partner, more than a million people--from spouses, partners, relatives, and friends to doulas, nurses, midwives, and childbirth educators--have relied on Penny Simkin's clear, concise, authoritative, and warm-hearted guidance as they care for the new mother from her last trimester through the early postpartum period. Including extensive updates on medical knowledge and practices, on changes in hospital and home-birth protocols, and on the role of parents' cultural backgrounds in shaping an ideal and satisfying birth plan, The Birth Partner remains the definitive guide to helping a woman through labor and birth and is the essential manual to have at hand during the event. Find thorough information on: Preparing for labor and knowing when it has begun -- Normal labor and how to help the mother every step of the way -- Epidurals and other medications for labor -- Pitocin and other means, including natural ones, to induce or speed up labor -- Non-drug techniques for easing labor pain -- Cesarean birth and complications that may require it -- Breastfeeding and newborn care...and much more. For the partner who wishes to be truly helpful in the birthing room, this book is indispensable."--Amazon.com.